Pengaruh Konsentrasi Surfaktan Campuran (Span 80 dan Span 20) dan Rasio Volume Emulsi/Fasa Eksternal terhadap Ekstraksi Ion Kadmium (Cd) Menggunakan Teknik Emulsi Membran Cair - Amin, Alif Hidayatullah; Hamzah, Baharuddin; Ningsih, Purnama (Universitas Tadulako, 2018)
Research on the extraction of cadmium(II) ion has been performed using the emulsion liquid membrane technique. This research used laboratory experimental method using benzoyl acetone as a carrier, kerosene as a membrane, nitric acid solution as an internal phase, span 80 and span 20 as a surfactant, and cadmium(II) solution as a sample. The present study was conducted to determine the optimum conditions of cadmium(II) ion extraction in solutions comprising variations in surfactant concentration of spans 80 and span 20 mixtures (1.5–3.5%) and variations in the ratio of emulsion/external phase (1:5–1:7). Determination of remaining of cadmium(II) ion concentration in the sample was analyzed using UV-Vis spectrophotometer at 519 nm wavelength. The results showed that the concentration of mixed surfactants (span 80 and span 20) which resulted in a maximum percent of extraction was 2.5% with 60.11% extraction percentage. In addition, the volume ratio of the emulsion/external phase gave a maximum extraction percentage at a ratio of 1:5.5 with an extraction percent of 78.03%.